A system dynamics simulation model to evaluate project planning policies. (3rd May 2020) - Shafieezadeh, Mahdi; Kalantar Hormozi, Mehdi; Hassannayebi, Erfan; Ahmadi, Loza; Soleymani, Marjan; Gholizad, Arezou
ABSTRACT: Computer simulation modeling approach has been used for the last decades to address the growing need for estimation, analysis and improvement of project performance indicators. In this research, a dynamic simulation model is developed capturing both hierarchical and dynamic complexities of projects. This paper discusses how changes in dynamics can influence the critical performance indicators of a project throughout its lifecycle. The designed simulation model is capable of assessing the robustness and suitability of the scope and change management policies. The validity of the model was tested by a real-world project in the petrochemical industry. The significant factors influencing a project's performance are investigated in the case study. The simulation results indicate that resource allocation decisions could be optimized to improve project performance indicators. The developed decision model can be regarded as a flexible and predictive tool in the construction industry with the purpose of explaining the dynamic behavior of a project. Abbreviation: SD: System Dynamics